2014
DOI: 10.1016/j.clml.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Elevated Levels of Serum Ferritin Before Chemotherapy in Patients With Non-Hodgkin Lymphoma

Abstract: Elevated levels of serum ferritin of 500 ng/mL or more as well as the use of chemotherapy regimens besides CHOP-like or RCHOP, a high-intermediate/high risk IPI, and a high level of beta2-microglobulin in NHL may be an important marker for predicting poor survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
(42 reference statements)
1
16
0
1
Order By: Relevance
“…Increased levels of circulating ferritin, the body's primary iron storage protein, have been reported in a wide range of malignancies [1316, 2628]; moreover, increased ferritin levels are often related to decreased survival time and more aggressive disease progression [29]. For example, increased serum ferritin levels have been associated with the incidence, development, and metastasis of primary lung cancer [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased levels of circulating ferritin, the body's primary iron storage protein, have been reported in a wide range of malignancies [1316, 2628]; moreover, increased ferritin levels are often related to decreased survival time and more aggressive disease progression [29]. For example, increased serum ferritin levels have been associated with the incidence, development, and metastasis of primary lung cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased serum ferritin levels have been associated with the incidence, development, and metastasis of primary lung cancer [14]. Moreover, serum ferritin level has also been shown to be a reliable prognostic indicator in hepatocellular carcinoma [13] and other malignancies [12, 16, 22, 23, 30, 31]. Furthermore, serum ferritin measurements have been combined with more traditional cancer biomarkers such as CEA (carcinoembryonic antigen) and AFP (alpha-fetoprotein) for use as a diagnostic and/or prognostic marker in several types of cancer [14, 32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Serum Ferritin concentration closely follows the activity of the malignant lymphomas [20]. Other research work [21] has shown that levels of Serum Ferritin higher than 500 ng/mL is an important marker for predicting poor survival outcomes for non-Hodgkin Lymphoma. Nevertheless, and up to our knowledge, Serum Ferritin levels have not been yet related to the treatment response of HL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the chemotherapy scheme of lymphoma, a classic chemotherapy method, which is still commonly used, is CHOP therapy, which consists of cyclophosphamide, doxorubicin, vincristine, and prednisone. However, using CHOP therapy, patient's survival have historically been poor, particularly in the case of aggressive NHL (Yoh et al, 2014). Since approved by FDA in 1997, the monoclonal CD20 antibody rituximab combinating with CHOP, called R-CHOP therapy, for the treatment of B-NHL represents one satisfactory example in rapid and widespread use (Harrison et al, 2014).…”
Section: Introductionmentioning
confidence: 99%